Comparison of the Effectiveness of Behavioral Activation and Its Combination with Mental Contrasting with Implementation Intentions on the Psychological Well-Being of Adolescent Girls with Depressed Mood - Mohammadi Elizei, Mona; Seirafi, Mohammad Reza; Taghdisi, Mohammad Hossein; Mohammadi Shirmahaleh, Fatemeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to compare the effectiveness of behavioral activation and its combination with mental contrasting with implementation intentions on the psychological well-being of adolescent girls with depressed mood. Materials and Methods: This quasi-experimental study employed a pretest–posttest–follow-up design with a control group. From among 300 questionnaires collected from lower secondary school girls in Karaj during the 2021–2022 academic year, 45 participants were randomly assigned to two experimental groups and one control group after screening and applying inclusion criteria. The first experimental group received a 10-session intervention of behavioral activation (each session lasting 90 minutes), while the second experimental group received a combined intervention of behavioral activation and mental contrasting with implementation intentions. The Beck Depression Inventory-II (BDI-II) was used for initial screening, and Ryff’s Psychological Well-Being Scale was administered at the pretest, posttest, and three-month follow-up stages. Data were analyzed using repeated measures analysis of variance, along with the Shapiro–Wilk, Levene’s, M. Box, and Mauchly’s sphericity tests, as well as the Bonferroni post-hoc test. All analyses were conducted using SPSS version 24 at a significance level of p < 0.01. In the final analysis, data from 40 participants were included. Findings: The mean differences in psychological well-being components between the two intervention groups (behavioral activation and its combination with mental contrasting with implementation intentions) and the control group were statistically significant. Both independent variables led to an increase in the mean scores of psychological well-being components. Additionally, a significant difference was observed between the effects of behavioral activation and the combined intervention on the components of self-acceptance (p = .041), autonomy (p = .042), and environmental mastery (p = .029). The combined intervention led to greater increases in these components compared to behavioral activation alone. Conclusion: Although behavioral activation is an effective method for enhancing psychological well-being in adolescent girls with depressed mood, its combination with mental contrasting and implementation intentions yields more substantial outcomes. Given the results of this study and the psychological challenges experienced by this age group, the use of these interventions is recommended to improve the psychological well-being of adolescent girls with depressed mood.